1995
DOI: 10.1183/09031936.95.08111975
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic bronchiolitis obliterans organizing pneumonia with multiple cavitary lung nodules

Abstract: Bronchiolitis obliterans organizing pneumonia (BOOP) is a pulmonary disorder with a wide spectrum of radiological features. We report the case of a 58 year old woman, in whom the radiological appearance was multiple cavitary nodules in both lungs, that responded with a complete resolution after corticosteroid therapy. This finding justifies the inclusion of BOOP in the differential diagnosis of multiple cavitary nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The presence of satellite lesions [73] Focal OP can also present as multiple mass-like opacities ( Fig. 4) [74,75,76]. This was the most frequent finding in one study in which the majority of cases were peripherally located and demonstrated a pulmonary vessel leading to a nodular opacity or a small bronchus entering the centre of the nodular opacity [77].…”
Section: Classical Cop: Clinical and Imaging Presentationmentioning
confidence: 97%
“…The presence of satellite lesions [73] Focal OP can also present as multiple mass-like opacities ( Fig. 4) [74,75,76]. This was the most frequent finding in one study in which the majority of cases were peripherally located and demonstrated a pulmonary vessel leading to a nodular opacity or a small bronchus entering the centre of the nodular opacity [77].…”
Section: Classical Cop: Clinical and Imaging Presentationmentioning
confidence: 97%
“…Possible pulmonary lesions included unilateral or bilateral patchy consolidations in subpleural or peribronchial distribution, multiple nodules, single nodule, or mass, etc. All of them may be with or without air bronchograms, cavitations, or reverse halo sign [8,[26][27][28][29][30][31][32]. However, in our opinion, at least half of all cases could be diagnosed much earlier if diagnosed properly.…”
Section: Discussionmentioning
confidence: 83%
“…There have been two case reports of patients presenting with multiple cavitary lung nodules [18,19]. In one case a 58-year-old female presented with a 2-month history of fever, weakness, cough and a high ESR [18].…”
Section: Discussionmentioning
confidence: 98%